PARAMETRIC SURVIVAL ANALYSIS OF TESTICULAR CANCER USING AN EXPONENTIAL MODEL WITH TYPE I CENSORED DATA - Idrus Syahzaqi; Ardi Kurniawan; Valerina Marischa Usmarasima; Aurora Gie Nur Wahyudi; Muhamad Zaky Ramadhani; Nuzzulia Calvina Izumy (Journal of Mathematics and Scientific Computing With Applications, 2026)
Quantitative prognostic evaluation is essential for testicular cancer, yet standard analyses often overlook model assumptions. This study evaluates patient survival times using a parametric exponential model under a type I censoring structure (n = 134, from cBioPortal). Parameter estimation via Maximum Likelihood Estimation yielded 82 uncensored and 52 censored observations. The Anderson-Darling test (p = 0.067) indicated statistical adequacy for the exponential distribution while the Weibull distribution was rejected (p < 0,010), confirming the assumption of a constant hazard, estimating a Mean Time to Failure of 64,54 months with a constant hazard rate of 0.0155 per month. However, these model-based estimates face critical clinical limitations. The small sample size and the rigid assumption of a constant hazard fail to capture the dynamic, time-varying biological progression of cancer. While this parametric approach provides a simplified baseline, clinical conclusions must be drawn cautiously; future research requires larger cohorts and flexible, non-constant hazard models to ensure actual clinical generalizability.